Pharmacokinetics‐based adherence measures for antiretroviral therapy in HIV‐infected Kenyan children. Issue 1 (15th June 2017) - Tu, Wanzhu; Nyandiko, Winstone M; Liu, Hai; Slaven, James E; Scanlon, Michael L; Ayaya, Samuel O; Vreeman, Rachel C
Abstract: Background : Traditional medication adherence measures do not account for the pharmacokinetic (PK) properties of the drugs, potentially misrepresenting true therapeutic exposure. Methods : In a population of HIV‐infected Kenyan children on antiretroviral therapy including nevirapine (NVP), we used a one‐compartment model with previously established PK parameters and Medication Event Monitoring Systems (MEMS®)‐recorded dosing times to estimate the mean plasma concentration of NVP (Cp) in individual patients during 1 month of follow‐up. Intended NVP concentration (Cp') was calculated under a perfectly followed dosing regimen and frequency. The ratio between the two (R = Cp/Cp') characterized the patient's NVP exposure as compared to intended level. Smaller R values indicated poorer adherence. We validated R by evaluating its association with MEMS®‐defined adherence, CD4%, and spot‐check NVP plasma concentrations assessed at 1 month. Results : In data from 152 children (82 female), children were mean age 7.7 years (range 1.5–14.9) and on NVP an average of 2.2 years. Mean MEMS® adherence was 79%. The mean value of R was 1.11 (SD 0.37). R was positively associated with MEMS® adherence ( p  < 0.0001), and lower‐than‐median R values were significantly associated with lower NVP drug concentrations ( p  = 0.0018) and lower CD4% ( p  = 0.0178), confirming a smaller R value showed poorer adherence. Conclusion : The proposed adherence measures, R, captured patient drug‐taking behaviours and PK properties.